Disease Control for Florida Tomatoes - Shouan Zhang; Mathews Paret; Ken Pernezny; Pamela Roberts (EDIS)
Successful disease management has always been vital in Florida tomato production, given the generally ideal environmental conditions for most plant diseases. An integrated disease management program is a successful approach.